Death Penalty for Corruptors in Indonesian Human Rights Perspective - Yaris Adhial Fajrin; Arista Putri Purnamasari; Ryvina Izza Rosyida; Dwi Faizah Maulidiyah (Unnes Law Journal, 2020)
The death penalty for corruptors, gaining a place in Indonesia's positive criminal law. As a country that makes Pancasila an ideology, it is interesting to be reviewed in this paper on the existence of the death penalty for the corruptor from a human rights perspective in Indonesia. Therefore, the author raised two issues, namely the first, how is the death penalty for corruptors in Indonesia's positive law? second, what about the death penalty for such corruptors if reviewed from a Human Rights perspective in Indonesia? To answer this, the authors chose legal research with a normative approach as part of its research methods. Based on the study obtained that the death penalty for corruptors does not conflict with Indonesian human rights values, because it is seen as the most serious crime. Even the formulation of the death penalty is currently seen as in line with the direction and ideals of reforming Indonesia's criminal law, which is increasingly humanist and puts forward the purpose of justice and benefit.